Mechanical Properties of Biocomposite Films Based Polyvinyl Alcohol/Potato Starch Filled by Coffee Ground Waste - Asrofi, Mochamad; Arisandi, Hilmy Dzaki; Pradiza, Revvan Rifada; Junus, Salahuddin; Mahardika, Melbi; Amanda, Putri; Ilyas, R.A.; Asyraf, M.R.M.; Salit @ Sinon, Mohd Sapuan (Unique Scientific Publishers, 2024)
Plastic is a ubiquitous material used to meet various human needs. However, its use negatively impacts the environment due to its non-biodegradability, contribution to pollution, and potential health threats. Biocomposite materials offer a promising solution to these problems. This study aimed to develop biocomposite films using a polyvinyl alcohol/ potato starch matrix reinforced with coffee grounds waste as a filler. This experimental study involved three tests: tensile testing, fracture morphological observation, and biodegradation in soil. The addition of CGW to the PVA/PS matrix increased tensile stress, reaching a maximum of 9.42MPa at a 2% filler loading. This result corresponded with the tensile modulus, which also peaked at 2% CGW (0.28MPa). Fracture morphological analysis via scanning electron microscopy confirmed these findings, revealing wave-like patterns and strong interfacial bonding between the matrix and filler at this concentration. The lowest tensile stress (6.31MPa) was observed at a 3% filler loading. Strain values remained relatively consistent between pure PVA and the biocomposites. Biodegradation testing revealed degradation rates of 32, 34, 36, 39, and 37% for PVA, PVA/PS, and CGW loadings of 1, 2, and 3%, respectively, after 15 days of soil burial. The biocomposite films, particularly at the optimal CGW loading, exhibit competitive tensile stress and biodegradation rates compared to synthetic plastics, suggesting their potential suitability for food packaging applications. © 2024, Unique Scientific Publishers. All rights reserved.